Komunikasi Pemasaran Agrowisata Alas Harum Tegallalang di Masa Pandemi Covid 19 - Made Ika Kusuma Dewi (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2022)
It has been two years since Indonesia has experienced the COVID-19 pandemic, this virus is growing rapidly. This incident has resulted in many tourism sectors that still rely on tourism to always innovate in their development, one of which is Alas fragrant agro-tourism. This fragrant pedestal agro-tourism is one of the popular agro-tourism objects. This fragrant pedestal agrotourism during the covid 19 pandemic was able to survive and there were no layoffs of employees in running their tourism business because it was driven by excellent marketing communication. The focus of this research is the marketing communication process for Alas Fragrant agro-tourism during the COVID-19 pandemic. The type of approach used in this article is a qualitative perspective. Instagram social media makes it easy for Alas Harum agro-tourism marketing to promote the products offered, Instagram users can see promos at Alas Harum Agro-tourism and hashtags on Instagram features are used as a measure of the effectiveness of marketing communications, using hashtags can be used as an implicit encouragement for consumers to engage in company promotion efforts